Integrasi Karakter Profil Pelajar Pancasila dalam Perangkat Pembelajaran Calon Guru Bahasa Indonesia - Anjas Rusdiyanto Soleh; Dini Restiyanti Pratiwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The aim of this research is to identify integration of the Profil Pelajar Pancasila in thelearning tools of prospective Indonesian teachers. This research uses qualitative researchby applying descriptive method. The data sources in this study is learning tools fromMicroteaching courses student university in Indonesian Language and LiteratureEducation study program, Faculty of Teacher Training and Education, MuhammadiyahUniversity of Surakarta. The data in this research is the form of parts in the learningdevice which is an integration of the Profil Pelajar Pancasila. Data collection techniquesused in this research are note-taking and documentation techniques. Analysis of the datain this study using content analysis techniques. The results of this study indicate that theintegration of the six aspects in the Profil Pelajar Pancasila is spread over several types oflearning tools in the form of Learning Implementation Plans, Student Worksheets, andassessment or evaluation instruments. By the three types of learning tools, the integrationof the Profil Pelajar Pancasila is contained in the learning steps in the LearningImplementation Plans, learning instructions in the Student Worksheets, and in theassessment aspect on assessment or evaluation instrument.